2014
DOI: 10.1371/journal.pone.0103389
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Remodeling in Response to Nitrogen Deprivation in the Microalgae Chlorella sp. (Trebouxiophyceae) and Nannochloropsis sp. (Eustigmatophyceae)

Abstract: Many species of microalgae produce greatly enhanced amounts of triacylglycerides (TAGs), the key product for biodiesel production, in response to specific environmental stresses. Improvement of TAG production by microalgae through optimization of growth regimes is of great interest. This relies on understanding microalgal lipid metabolism in relation to stress response in particular the deprivation of nutrients that can induce enhanced TAG synthesis. In this study, a detailed investigation of changes in lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
81
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 48 publications
17
81
2
Order By: Relevance
“…Nevertheless, the decrease in the other lipid classes is not equivalent to the increase in the content of the neutral lipids. This observation implies that, aside from the rearrangement of some polar lipids to form neutral lipids, de novo fatty acid synthesis is also induced (Martin et al, 2014;Simionato et al, 2013).…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, the decrease in the other lipid classes is not equivalent to the increase in the content of the neutral lipids. This observation implies that, aside from the rearrangement of some polar lipids to form neutral lipids, de novo fatty acid synthesis is also induced (Martin et al, 2014;Simionato et al, 2013).…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 95%
“…Martin et al (2014) showed a 52% increase in the total lipid of nitrogen-depleted Nannochloropsis sp. Furthermore, Bondioli et al (2012) observed a 75% increase in the lipid content for the nitrogen depleted Nannochloropsis sp.…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in TAG inversely track with the decline in C20:5 FA concentrations in both cell types (Supplemental Figures 7C and 7D). In P. tricornutum and other microalgae, the decrease in C20:5 FA during N-stress is believed to reflect the efforts by alga to pursue a second source for TAG by recycling C20:5 and C16 FA moieties from chloroplast thylakoid membrane glycerolipids (Abida et al, 2015;Li et al, 2012;Martin et al, 2014;Simionato et al, 2013). Specific galactoglycerolipid lipases, known in plants as patatin lipases (reviewed in Scherer et al, 2010), have been functionally characterized in C. reinhardtii and Nannochloropsis oceanica Li et al, 2014) as thylakoid glycerolipid recyclers.…”
Section: Nitrate-replete Conditions Trigger Biosynthesis Of Lipids Inmentioning
confidence: 99%
“…Lipid accumulation in several algal species is triggered by nitrogen (N) depletion, and these conditions have been heavily investigated to understand lipid metabolism regulation (Miller et al, 2010;Simionato et al, 2013;Li et al, 2014;Lu et al, 2014;Martin et al, 2014;Abida et al, 2015;Jia et al, 2015). Nitrogen deprivation also leads to accumulation of storage sugars like starch or chrysolaminarin, depending on the organism (Jia et al, 2015), and the impairment of the storage sugar metabolism was observed to further increase TAGs (Blaby et al, 2013).…”
mentioning
confidence: 99%